THE RELATIONSHIP BETWEEN PATIENT SATISFACTION AND THE QUALITY OF SERVICES INGENERAL HOSPITAL OF MUHAMMADIYAH UNIVERSITY OF JEMBER - Suryani, Yulita Erma; Toni Herlambang; Mohammad Thamrin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The purpose of this study was to determine the relationship between patient satisfaction with the quality of nursing services at the Muhammadiyah University General Hospital Jember. Method: The research methodology used a cross sectional research design with the type of correlation test. The sample of this study used quota sampling with a total of 84 respondents. Using Chi-Square statistics with a p-value of less than 0.05. Results: Research findings showed that the quality of nursing services with good quality and patient satisfaction with satisfied quality. The result of the Chi-Square Test is p = 0.020 and the contingency coefficient is 0.374. Based on the results of the study, there is a stronger relationship between the Quality of Nursing Services in clinics in Jember province with Hospitalized Patients. Novelty: Satisfaction is a model of balancing between expectations (performance standards that must be followed) with the actual performance performed by employees, as well as the subjective value satisfaction expressed by patients after receiving health services. Nursing service quality is an important component for health care institutions to meet the needs and expectations of patients. Good quality nursing services will increase client satisfaction. It is expected that this study will increase the willingness of hospital staff to provide patient care.